2018
DOI: 10.2196/resprot.9420
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Rehabilitation for Cognitive Impairment: Randomized Controlled Feasibility Trial

Abstract: BackgroundNonpharmacological interventions are needed to support the function of older adults struggling with subjective cognitive impairment (SCI), mild cognitive impairment (MCI), and dementia due to Alzheimer disease (AD). Telerehabilitation aims to provide rehabilitation at a distance, but cognitive rehabilitation by videoconferencing has not been explored.ObjectiveThe objective of this study was to compare goal-oriented cognitive rehabilitation delivered in-person with videoconferencing to determine wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 61 publications
(88 reference statements)
2
33
0
1
Order By: Relevance
“…We found that delivering the PrAISED intervention using Q Health was feasible and acceptable from the perspectives of clients, caregivers, and therapists. Similar findings have been reported by Burton and Nissen [ 37 , 38 ], who found that tele-rehabilitation was helpful with clients with cognitive impairments but required frequent modifications. One of the major barriers found in this study was the lack of digital literacy and access amongst clients with dementia and their caregivers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that delivering the PrAISED intervention using Q Health was feasible and acceptable from the perspectives of clients, caregivers, and therapists. Similar findings have been reported by Burton and Nissen [ 37 , 38 ], who found that tele-rehabilitation was helpful with clients with cognitive impairments but required frequent modifications. One of the major barriers found in this study was the lack of digital literacy and access amongst clients with dementia and their caregivers.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies with cognitively impaired adults have also shown that there might be added benefits in using video—as opposed to telephone—support [ 37 , 38 , 40 , 41 ]. Video calling might enhance users’ satisfaction [ 42 ], facilitate the development of therapeutic alliance, which is instrumental for intervention uptake and adherence [ 43 ], and promote the empowerment of a client with dementia, who might have difficulty communicating with the therapist without face-to-face contact.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect that we see in previous studies may be related to the adequate treatment of dementia while deprescribing medications to increase quality of life and potentially reduce the risk of medication-induced delirium episodes. Indeed, the multidisciplinary team approach of caring for rural dementia patients using CVT includes social work [27] and physical therapy [28]. The data from our CVT consultation service providing psychiatric and dementia specialist support to rural primary care physicians is further evidence of effectively providing remote dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that persons living with moderate cognitive impairment will need remote training from an expert in cognitive rehabilitation. Common techniques from cognitive rehabilitation can train people to use new technology, even if they have marked anterograde amnesia [ 17 ], and cognitive rehabilitation can be delivered remotely to persons living with mild cognitive impairment or mild to moderate dementia [ 18 , 19 ]. If cognitive rehabilitation is needed to train persons living alone with mild cognitive impairment or dementia to use videoconferencing and this intervention support is not available, we recommend engaging the telehealth suites if they are available through local health care agencies or use the telephone for your remote research.…”
Section: Remote Contact: How To Do Itmentioning
confidence: 99%